Journal of Mathematics Teacher Education - Chapman, Olive; Potari, Despina; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Mathematics Teacher Education (JMTE) is devoted to research into the education of mathematics teachers and development of teaching that promotes students' successful learning of mathematics. JMTE focuses on all stages of professional development of mathematics teachers and teacher-educators and serves as a forum for considering institutional, societal and cultural influences that impact on teachers' learning, and ultimately that of their students. Critical analyses of particular programmes, development initiatives, technology, assessment, teaching diverse populations and policy matters, as these topics relate to the main focuses of the journal, are welcome. All papers are rigorously refereed. Papers may be submitted to one of three sections of JMTE as follows: Research papers: these papers should reflect the main focuses of the journal identified above and should be of more than local or national interest. Mathematics Teacher Education Around the World: these papers focus on programmes and issues of national significance that could be of wider interest or influence. Reader Commentary: these are short contributions; for example, offering a response to a paper published in JMTE or developing a theoretical idea. Authors should state clearly the section to which they are submitting a paper. As general guidance, papers should not normally exceed the following word lengths: (1) 10,000 words; (2) 5,000 words; (3) 3,000 words. Maximum word lengths exclude references, figures, appendices, etc. Critiques of reports or books that relate to the main focuses of JMTE appear as appropriate.
Keywords: Philosophy and social sciences; Mathematics -- Study and teaching; Teaching; Mathematics Education; Teaching and Teacher Education; Philosophy of Education